Anti-freeze effect of Enoki mushroom extract on the quality preservation of frozen whipped cream. (February 2021) - Arai, Naoki; Fujiwara, Ayako; Wakuda, Michiyo; Fujimoto, Toshihiro; Nambu, Yuko; Ishii, Toya; Matsumiya, Kentaro; Matsumura, Yasuki; Kawahara, Hidehisa; Ogino, Koji
Abstract: The alkaline extract of Enoki mushroom ( Flammulina velutipes ) has been shown to have ice crystal growth inhibiting activity, and its beneficial effect on the quality preservation of frozen foods is highly expected. The purpose of this study was to investigate the effect of Enoki mushroom extract which has an ice recrystallization inhibiting activity on the quality of frozen whipped creams. Whipping creams with different milk/vegetable fat compositions were prepared. The proportion of % milk fat and % vegetable fat was given as follows; 0:37, 10:28, 20:20 and 40:0, respectively. Whipped foam samples were frozen and stored at −20 °C, then the effect of adding 0.1% Enoki mushroom extract was tested. Fresh dairy flavor and smooth melt in mouth texture was deteriorated during the course of frozen storage for 37 days, and the frequency is higher in whipped creams with high milk fat content. Addition of 0.1% Enoki mushroom extract ameliorated these quality changes and significantly retained moisture content. Microscopic observation of the internal structure of frozen foam samples by cryo-SEM revealed that the ice crystal aggregates grown in the emulsified solid phase were reduced by adding Enoki mushroom extract. GC/MS analysis of the flavor components revealed that the content of furan compounds (furfural and 2-furanmethanol) was increased by 1.7 times in control foam samples during frozen storage, whereas the furan compounds in whipped foam sample containing Enoki mushroom extract did not increase after frozen storage. Based on these findings, it is proposed that ice crystal growth at the emulsified solid phase causes the sublimation of water on the surface of frozen whipped cream and destruction of the network structure of fat globules results in the quality changes after thawing. Enoki mushroom extract was found to retard ice crystal growth in whipped cream, thus supposed to reduce the quality changes during frozen storage. Highlights: Alkaline extract of Enoki mushroom exhibited an ice recrystallization inhibiting activity. Addition of Enoki mushroom extract reduced the quality changes of whipped cream during frozen storage. Ice crystal growth inhibition was identified by cryo-SEM observation at the emulsified solid phase of frozen whipped cream.